Treatment of mallet fingers in Dutch hospitals: a nationwide survey of practice. (June 2015) - Haagsma, Annet; de Boer, Herman L.; Quintus, Astrid C.; Strikkeling, Nicolette J.M.; Zeebregts, Clark J.; Smit, Jeroen M.
Abstract : Objective: The aim of this study was to create an overview of the treatment of mallet fingers in Dutch hospitals. Methods: A national online questionnaire was used to determine the treatment of mallet fingers in Dutch emergency units. Results: Data were received from 58 units (response rate 97%). All the emergency units treated an uncomplicated mallet finger with a splint. The treatment of complicated mallet fingers was less uniform. The departments of general, orthopaedic and plastic surgery were involved in the treatment and their involvement varied according to the type of mallet finger and showed variations in the follow-up treatment. Conclusion: There is a general consensus on the treatment of uncomplicated mallet fingers. The follow-up treatment of uncomplicated lesions as well as the treatment of complicated mallet fingers should be fields of future research.